Bilateral Choroidal Detachment Following Pseudophakic Cystoid Macular Edema Treatment with Oral Acetazolamide - Agnieszka Kudasiewicz-Kardaszewska; Małgorzata Ozimek; Tomasz Urbański; Sławomir Cisiecki (Life)
Aim: This case report presents an unusual instance of bilateral choroidal effusion following the oral administration of acetazolamide for the treatment of pseudophakic cystoid macular edema (PCME). Case Presentation: An 87-year-old Caucasian man experienced sudden, painless vision loss in both eyes several days after beginning treatment for PCME in his left eye. He had undergone uncomplicated cataract surgery in both eyes two months earlier. The treatment regimen included oral acetazolamide (250 mg twice daily) and topical pranoprofen, a nonsteroidal anti-inflammatory drug (NSAID). One week after the initiation of acetazolamide treatment, the patient suffered a marked decline in visual acuity. Bilateral choroidal effusion was diagnosed. Prompt discontinuation of acetazolamide and initiation of topical dexamethasone (1% hourly) and atropine (1% twice daily) resulted in rapid clinical improvement. Conclusions: Carbonic anhydrase inhibitors (CAIs) such as acetazolamide, although commonly used to manage intraocular pressure, can cause choroidal effusion—a rare but potentially sight-threatening complication. Ophthalmologists should exercise caution, particularly in elderly patients, and be alert to early signs of this adverse effect. Early diagnosis and prompt management are essential to prevent permanent visual damage. To our knowledge, this is the first reported case of bilateral choroidal detachment associated with acetazolamide in the context of PCME.